2016
DOI: 10.1167/iovs.16-19402
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis by miR-122 in Pterygium via Targeting Bcl-w

Abstract: Decreased expression of miR-122 in pterygium might result in abnormal cell apoptosis via its regulation of the expression of Bcl-w, and subsequently contribute to the development of pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Several reports have revealed the putative contribution of BCL-w in other types of cells. Abundant expression of BCL2L2 was found within the whole epithelium and blood vessels of pterygium, in contrast to the presence of BCL-w protein predominantly in the basal layer of epithelium in normal conjunctiva 88 . Recently, it was also shown that BCL2L2 overexpression contributed to the survival of megakaryocytes and increased formation of platelets 87 .…”
Section: Role Of Bcl-w In Normal Cells and Non-cancer Diseasesmentioning
confidence: 78%
“…Several reports have revealed the putative contribution of BCL-w in other types of cells. Abundant expression of BCL2L2 was found within the whole epithelium and blood vessels of pterygium, in contrast to the presence of BCL-w protein predominantly in the basal layer of epithelium in normal conjunctiva 88 . Recently, it was also shown that BCL2L2 overexpression contributed to the survival of megakaryocytes and increased formation of platelets 87 .…”
Section: Role Of Bcl-w In Normal Cells and Non-cancer Diseasesmentioning
confidence: 78%
“…promotes cell invasion, migration, and growth via repression the expression of PTEN, MMP-2 and MMP-9 (32). MiR-122 promotes cell apoptosis and inhibits apoptosis by targeting FOXO and inducing Bcl-w (33,34). Upregulation of miR-24 promotes cell proliferation by targeting MEN1 and regulates cell growth and apoptosis by targeting BCL2 (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from tissues and PTFs with Trizol or Purelink RNA mini kit for reverse transcription and PCR amplification as described previously (Cui et al, ; Li et al, ). PCR primers were as folllows: (a) for MMP‐9, 5′‐GCGTCTTCCCCTTCACTTTC‐3′ (Forward) and 5′‐ATAGGGTACATGAGCGCCTC‐3′ (Reverse); (b) for HuR, 5′‐CCAACTTGTACATCAGCGGG‐3′ (Forward) and 5′‐GGCTGCAAACTTCACTGTGA‐3′ (Reverse); (c) for glyceraldehyde 3‐phosphate dehydrogenase (GAPDH), 5′‐GTCAGTGGTGGACCTGACCT‐3′ (Forward) and 5′‐TGCTGTAGCCAAATTCGTTG‐3′ (Reverse).…”
Section: Methodsmentioning
confidence: 99%
“…bio-rad.com/en-us/product/quantity-one-1-d-analysis-software; RRID:SCR_014280.) 2.12 | RT-PCR and quantitative real-time PCR analysis Total RNA was isolated from tissues and PTFs with Trizol or Purelink RNA mini kit for reverse transcription and PCR amplification as described previously (Cui et al, 2016;Li et al, 2017). PCR primers were as folllows:…”
Section: Gelatin Zymographymentioning
confidence: 99%